Strengthening the Pedagogical Competence of Islamic Religious Education (PAI) Teachers: Mentoring Preparation of Contextual and Deep Learning-Based Teaching Modules in Banyuasin Regency - Fitri Oviyanti; Nurlaila; Faizatul Mabruroh (Unram Journal of Community Service, 2026)
The rapid implementation of the Merdeka curriculum in Indonesia requires Islamic Education (PAI) teachers to design contextual teaching materials that promote meaningful and deep learning. However, many teachers in Banyuasin Regency still face challenges in developing such modules. This community service aimed to enhance the pedagogical competence of PAI teachers through mentoring in developing contextual and deep learning based teaching modules. The activity employed a participatory mentoring approach consisting of training session, workshops, and group guidance. The results indicate an increase in teacher’s knowledge, creativity, and abilities in designing contextual modules. This program strengthens their pedagogical competence and encourages reflective teaching practices that align with the principles of in-depth learning.